ANALYSIS OF MENTAL HEALTH LITERACY AND ATTITUDES TOWARD SUBSTANCE USE AMONG UNIVERSITY GOING STUDENTS: A CROSS-SECTIONAL STUDY - Yadav, Anmol; Singh, Aman Kumar; Kumar, Ashish; Choudhary, Swati; Dhull, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Substance use among university going students is a major public health issue in developing countries. We performed a cross-sectional study to assess the mental health literacy and attitude towards addiction among the university students. For the collection of the data Knowledge and Attitude Addiction Questionnaire for Adolescents (KAAQA), a self-reported questionnaire was used. In the survey responses of 430 (male and female) students were taken into consideration. The result reveals a concerning trend of positive misconceptions regarding substance use also females exhibited a significantly higher demand for preventative information compared to the male. Despite differences often expected, results reveal similar patterns between men and women on nearly all KAAQA measures. Responses stay close in range, pointing to shared understanding about substance use regardless of sex. What stands out is how little variation appears when comparing answers by gender. This closeness implies efforts aimed at education or prevention might work equally well without tailoring to one group. Little evidence supports designing separate approaches just based on gender alone.